Adaptive responses of human skeletal muscle to vibration exposure - Bosco, C.; Cardinale, M.; Rolli, R.; Introini, E.; Tihanyi, J.; Duvillard, S. P.; Iacovelli, M.; Viru, A.
The study was performed in order to test the possibility wheather a single whole body vibration (WBV) session will produce human skeletal muscle response. In 6 female volleyball players movement velocity, muscle force and power were recorded when they performed maximal leg press exercises with extra load of 70,90,110 and 130 kg. The testing took place before and after a 10-min WBV exposure. During WBV subjects were in the standing position with the toes of one leg on the vibration platform (E leg) while the other leg (C leg) was risen from the ground. WBV induced statistically (P<O.O5) significant improvement of the movement velocity, muscle force and power. In result-, the velocity-force and power-force curve were shifted to the right. C leg failed to show changes in studied mechanical variables after the WBV session. In conclusion, the acute effect of a short term WBV on neuromuscular apparatus is expressed by improved movement velocity, muscle force and power in performing leg press exercise with external loads.